Prioritization of Climate Smart Practices for Cocoa in Peru: Climate analysis and Cost Benefit Analysis of climate smart practices in cacao production in Peru to evaluate the adaptation and scaling potential - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Climate change has been projected to change the geography of cocoa production in Peru unless production practices are adapted to novel conditions. Climate change impacts are site specific and each household has a different set of assets and constraints. This study provides a climate hazard based Climate Smart Agriculture (CSA) practice prioritization and cost-benefit analysis for cocoa in Peru, Latin America. We reviewed projected climatic change risks, provide an overview of potential CSA practices and demonstrate the relative profitability of CSA systems using a Cost-Benefit Analysis (CBA), involving the comparison of the annual flows of incremental benefits with that of incremental costs. Climate- smart agriculture (CSA) is an approach to confront the new challenge of climate change (Lipper et al., 2014). It expands the concept of sustainability of agricultural production by adding adaptation to climate change and mitigation of GHG emissions from production as a new dimension. In CSA the sustainable intensification of production by efficiently using available resources is the priority. The second pillar is adaptation of production systems to climate changes. Third, the mitigation element emphasizes explicitly the reduction of GHG emissions from the production of cocoa by using alternative practices. The CSA concept accounts for synergies and trade-offs between the three objectives. For example, the sustainable improvement of cocoa productivity on existing land will be an important contributor to the reduced conversion of forest to cocoa production.